The Influence of Financial Literacy and Digital Literacy on the Increase in the Class of Msmes Registered in the Bri Growpreneur Program - Ismet Sarmen (Eduvest - Journal of Universal Studies, 2025)
Study This aim For analyze the influence of financial literacy and digital literacy on increase class of Micro, Small and Medium Enterprises (MSMEs) that are incorporated in the BRI Growpreneur program . Approach study use method quantitative with data collection through survey against 97 respondents , which was determined use Slovin's formula . Data analysis was carried out with multiple linear regression For test connection between variables . Research results show that digital literacy has influence positive and significant to increase MSME class . Findings This indicates that the more tall ability perpetrator business in control digital technology , increasingly big opportunities for MSMEs to move up a class through improvement efficiency , power competitive , and market expansion . On the other hand , financial literacy does not proven influential significant to increase MSME class . This show that although perpetrator business own understanding good finances , factors​ the Not yet Enough strong For push transformation business in a way directly . Findings study This strengthen human capital theory which emphasizes importance mastery skills practical and relevant , especially digital literacy , in increase capacity business . Study results This expected can become input for government , institutions finance , as well as development program organizer in designing more interventions​ effective For encouraging MSMEs to move up a class in the digital era.